Public elementary schools' handling of student neglect and adjustment problems - Ikhrom, Ikhrom; Dalmeri, Dalmeri; Wahyuni, Endang; Kafipour, Reza (Frontiers in Education, 2023)
The issue of student adjustment has become a serious challenge for education due to the schools’ ignorance. Unfortunately, elementary schools in Indonesia still lack special mechanisms and staff for handling student adjustment. Therefore, the current study researchers would like to uncover the student neglect in the policy, the school competence, and the adjustment within the public elementary school and analyze the conditions that trigger student neglect. The primary data supporting the qualitative research were gathered from sixteen public elementary schools in Semarang and Surabaya. The data were collected through documentation, interview, and observation. The study results showed no specific adjustment case-handling regulations and mechanisms, specialized adjustment case-handling professional staff, and specific room for adjustment case-handling activities within the public elementary school due to the unawareness, the misunderstanding, the ignorance, the less-caring educational system, and also the disconnection and the neglect of the relationship between the educational institution and the community. The study results imply that the student neglect of adjustment within the public elementary school fails the educational institution to enhance the students’ achievement and personality and deteriorates the students’ psychological conditions in the future.